EVALUASI INTERVENSI PERAWATAN PALIATIF PADA PENDERITA KANKER TERMINAL DEWASA DI RSUPN DR. CIPTOMANGUNKUSUMO - Putranto R.; Laksono Trisnantoro; Hendra Y. (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: Cancer is one of the catastrophic diseases whichhave the characteristics of high cost, high volume, and high risk.Based on Basic Health Research (Riskesdas) 2013, 65%among 240.000 new cases of advanced cancer per year areseeking medical assistance where the curative treatment nolonger effective. Palliative care is an approach that is no longereradicates the disease, in contrary, it's an approach to increasethe quality of patient's life until the end of life period (death).Objective: This research aimed to evaluate the correlation oflength of stay (LOS) and direct cost of terminal cancer patientswho get palliative intervention or not receive palliativeintervention.Methods: This study used a retrospective cohort design whichinvolving 120 patients (29 cases and 91 controls) that takenfrom medical records of hospitalized patient in CiptoMangunkusumo Hospital (RSCM). The inclusion criteria consistof patient has been diagnosed as terminal cancer disease, aged≥18 years, and palliative care consultation.Results: The results of the bivariate analysis using Mann-Whitney test showed a significant correlation between directcost and palliative intervention (p-value = 0,041) and nosignificant relationship between length of stay (LOS) andpalliative intervention (p-value = 0,873).Conclusion: There was a significant relationship betweenpalliative intervention and room expenditure rates, visites,actions, and drugs. Therefore, it's necessary to further researchto explore variables that influence LOS and direct cost inpalliative care intervention patients with terminal cancer.